Prevalence of Metabolic Syndrome in Military Police Officers of São Paulo City: The Health Promotion in Military Police (HPMP) Study - Souza, Diego Ribeiro de (2021)
We determined the prevalence of metabolic syndrome (MetS) among military police officers (MPOs) from the radio patrol program of the Military Police of Sao Paulo State (PMESP). Towards this goal, we analyzed the following characteristics: shift duty (daytime or nighttime patrol), service length in the PMESP, education level attained, weekly alcohol consumption, smoking, and physical activity of 93 MPOs. The MPO groups were created based on work shift [daytime (n=48) or nighttime (n=45)], and years of MPO experience [≤3 years (n=48) or ≥10 years (n=45)]. The overall prevalence of MetS among the 93 MPOs was 43%. There was a higher prevalence of MetS in the group with ≥ten years (53.3%) than that with ≤three years (33.3%); so, 1,6 times higher. The more prevalent MetS indicators (n=93) included waist circumference (76.3%), hypertension (55.9%), reduced plasma HDL-cholesterol levels (44%), hypertriglyceridemia (32.2%), and hyperglycemia (20.4%). Greater waist circumference, hypertension, hypertriglyceridemia, higher glycated hemoglobin A1c (HbA1c) levels, and MetS itself were associated with the service length (i.e., ≥ten years). The work shift was not associated with any MetS indicator. Those who were overweight or obese were 2.2. times more likely to develop MetS. Hypertriglyceridemia, the best indicator of the MetS, increased the chance of developing MetS by 16 times. Conclusion: MPOs exhibit a high prevalence of MetS, associated with the years of service and age.